Курганы бассейна Крынки (центральный Донбасс и северо-восточное Приазовье) - Полидович, Ю.Б.; Абдрахманов, Д.В. (Археологический альманах, 2004)
This paper is devoted to the analysis of the Krynka river basin barrows. This basin is an important part of the Central Donbass and Northeastern Azov geographical regions. Many barrows can be found here. Their quantity and parameters are dependent on an arrangement in certain place of pool. The most significant barrows are located on the upstream of the river and include primarily Late Bronze Age burials of the timber-grave culture as well as medieval nomads. The barrows on the average and bottom current of the river Krynka arc more varied.